EFEKTIVITAS PEMBERIAN MULSA VERTIKAL PADA SALURAN TERAS GULUDAN UNTUK MENURUNKAN LAJU LIMPASAN DAN EROSI PADA BERBAGAI KEMIRINGAN LAHAN (SKALA LABORATORIUM) - , ISTI YAYUK BASUKI, Dr. Ir. Sunarto Goenadi, DAA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Organic wastes are often found on farms such as straw, weeds, twigs, leaves, stems, and so on. This wastes in addition to animal feed is usually just thrown away or burned away, but this organic waste can be used as organic mulch in several studies proved effective in reducing the rate of runoff and erosion. Conventional mulch mulching is a method in which an organic mulch is spread on the surface, and this method is often applied to agricultural land, but the application is still less effective mulch applied on slopes. It therefore appears that the idea of vertical mulch organic mulch placed in the canal or rorak mulch usually is combined with making mounds. This study compared the effect of vertical mulching on ridges channel the rate of runoff and erosion on the slope of 5 °, 10 °, and 15 ° with the use of straw as a mulch. And it turns vertical mulching on ridges channels proved to increase the effectiveness in reducing the rate of erosion, but less effective in reducing the rate of runoff when compared to the mounds without mulch because the land 5 °, 10 ° where mulch actually increase the amount of runoff. Vertical mulching most effectively applied on slope of land 15 ° .